Comparative Analyses of Fertility Evolution in Iasi County - Ana-Maria Amariei (CES Working Papers, 2015)
Iasi County has seen, in the last twenty-three years, a decline of the general fertility rate both in the urban region and in the rural region which leads to a decrease in the number of inhabitants and the aging of the population. The purpose of this study is to compare the trend of the general fertility rate, GFR, among the main age groups of fertile women, between 1990 and 2013. In order to accomplish this goal, we use time series analysis. Our results show that the GFR series presents a decreasing trend, from 70.6 children at 1000 women in 1990 to almost half in 2013. Future studies should investigate the determinant factors of this decline for GFR in Iasi County, we will investigate the influence of income, of unemployment and of level of education on general fertility rate (GFR).
Keywords: J11; J13; 330; Fertility; GFR; Time Series Analysis; ARIMA